The Nutraceutical Value of Carnitine and Its Use in Dietary Supplements - Alessandra Durazzo; Massimo Lucarini; Amirhossein Nazhand; Selma B. Souto; Amélia M. Silva; Patrícia Severino; Eliana B. Souto; Antonello Santini (Molecules, 2020)
Carnitine can be considered a conditionally essential nutrient for its importance in human physiology. This paper provides an updated picture of the main features of carnitine outlining its interest and possible use. Particular attention has been addressed to its beneficial properties, exploiting carnitine’s properties and possible use by considering the main in vitro, in animal, and human studies. Moreover, the main aspects of carnitine-based dietary supplements have been indicated and defined with reference to their possible beneficial health properties.